The ADOR mechanism for the synthesis of new zeolites - Eliášová, Pavla; Opanasenko, Maksym; Wheatley, Paul S; Shamzhy, Mariya; Mazur, Michal; Nachtigall, Petr; Roth, Wieslaw J; Morris, Russell E; Čejka, Jiří (Chemical Society reviews, 2015)
A novel methodology, called ADOR (assembly-disassembly-organisation-reassembly), for the synthesis of zeolites is reviewed here in detail. The ADOR mechanism stems from the fact that certain chemical weakness against a stimulus may be present in a zeolite framework, which can then be utilized for the preparation of new solids through successive manipulation of the material. In this review, we discuss the critical factors of germanosilicate zeolites required for application of the ADOR protocol and describe the mechanism of hydrolysis, organisation and condensation to form new zeolites starting from zeolite UTL. Last but not least, we discuss the potential of this methodology to form other zeolites and the prospects for future investigations.